Adaptasi Institusi Pendidikan Islam Berbasis Pesantren Terhadap Ekonomi Kapitalistik - Noer Syo Im; Achmad Muhibin Zuhri (Jurnal Budi Pekerti Agama Islam, 2024)
Islamic boarding schools as traditional Islamic educational institutions in Indonesia have experienced various challenges and changes along with the times. One of the challenges faced is the emergence of a capitalistic economy which emphasizes aspects of competition, efficiency and profit orientation. This research aims to explore how Islamic boarding school-based educational institutions adapt to a capitalistic economy without sacrificing the values ​​and basic principles of Islamic teachings. Using a qualitative approach, this research involved participant observation, in-depth interviews, and literature studies at several Islamic boarding schools in Indonesia. The research results show that Islamic boarding schools have implemented various adaptation strategies, such as diversifying funding sources, implementing modern management, and developing business units that are in line with Islamic values. However, Islamic boarding schools also face challenges in maintaining a balance between spiritual and economic aspects, as well as maintaining the distinctive identity and characteristics of Islamic boarding schools. This research contributes to the understanding of the dynamics of Islamic educational institutions in facing global economic changes and provides recommendations for future policy and practice.